Supervisi Akademik Pada Guru Sebagai Langkah Peningkatan Mutu Madrasah - Mu'alimin Mu'alimin; Sarwan Sarwan; Imron Rosady (Universitas Muhammadiyah Sidoarjo, 2019)
This paper aims to examine the academic supervision of teachers as a step to improve the quality of madrasas. The teacher has an essential role in improving the quality of learning. Teacher quality will significantly affect the quality of knowledge and the resulting output. However, teachers must have capable abilities based on pedagogical, professional, social, and personality competencies. Academic supervision is a routine activity that must be carried out by supervisors and madrasa heads, so the role of supervisors to supervise and foster is very much needed. The part of supervisors is still not maximized in conducting supervision and coaching. This situation has an impact on the quality of teachers in the teaching and learning process, not only that it will affect the quality of madrasas.